Methodical approaches to obtaining fraction of trypsin-like enzymes from marine aquatic organisms (on the example of Antarctic krill) - D. V. Gladun; A. N. Savchuk; L. I. Ostapchenko (Ukrainian Antarctic Journal, 2013)
The rapid development of biotechnology and pharmacology of the our days, one way or another, related to the targeted search of biologically active substances in the tissues of a wide variety of organisms, including the antarctic marine organisms. This group of organisms has attracted the attention of researchers due to its scarcity, as well as the presence of various protein composition. A promising direction is the creation of pharmaceutical products, based on proteins extracted from tissues of antarctic marine animals. Of particular interest is the possibility of molecules with directed action – enzymes with different specificity. In our work submitted the development methodological approaches for the isolation and testing fraction of trypsin-like enzymes from the tissues of the antarctic krill (Euphausia superba).